2010
DOI: 10.1111/j.1095-8649.2010.02656.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and ontogenetic shifts in the diet of Arctic charr Salvelinus alpinus in a subarctic lake

Abstract: Arctic charr (Salvelinus alpinus (L.)) is a cold-adapted salmonid fish with a wide circumpolar distribution. Due to its wide fundamental trophic niche (i.e. diet and habitat use), Arctic charr can be used to study energy flow as well as competitive and predator-prey interactions in subarctic lakes. The objective of this thesis was to evaluate how the trophic niche of Arctic charr in subarctic lakes is influenced by various biotic (e.g. intra-and interspecific resource competition and predation) and abiotic (e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 123 publications
5
65
0
Order By: Relevance
“…Therefore, we could only compare the data of the stomach content analysis to that of stable isotopic analysis conducted in the present study. We investigated diet shifts with a combination of stomach content and stable isotopic analysis, the results demonstrated that the diet shifts occurred when the body length of L. elongata was increased, which is consistent with findings for other fish species (Bacha and Amara 2009; Eloranta et al 2010;Santiago et al 2010). Metabolic rate directly impacts the food demand of fish (Moyle 2004) with metabolic rate of larger individuals slower than that of smaller individuals (Sims 1996).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Therefore, we could only compare the data of the stomach content analysis to that of stable isotopic analysis conducted in the present study. We investigated diet shifts with a combination of stomach content and stable isotopic analysis, the results demonstrated that the diet shifts occurred when the body length of L. elongata was increased, which is consistent with findings for other fish species (Bacha and Amara 2009; Eloranta et al 2010;Santiago et al 2010). Metabolic rate directly impacts the food demand of fish (Moyle 2004) with metabolic rate of larger individuals slower than that of smaller individuals (Sims 1996).…”
Section: Discussionsupporting
confidence: 70%
“…N values of L. elongata were observed in this study, and this phenomenon has also been found in other fish (Eloranta et al 2010;Zhang et al 2013). The δ 13 C values were the highest in spring and the lowest in summer, and the δ 15 N values in autumn were higher than any other season and were lowest in winter, probably related to the diet shift of L. elongata.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…The sampling of fish muscle tissue for SIA was performed in the late open-water season to examine the main food sources assimilated during the main growth period (Perga and Gerdeaux 2005; Eloranta et al. 2010; Hayden et al. 2014b).…”
Section: Methodsmentioning
confidence: 99%
“…Fishes also show flexible feeding habits and sometimes undergo diet shifts that deviate from their presumed food sources [17], e.g., shifts between the benthic and planktonic food webs [18], [19]. Among fish, for instance, ontogenetic changes in resource use is a common feature during their life cycle [5], [20]. Diet shifts of fishes are usually due to migration, size-related morphological constraints, habitat use and other reasons [21], [22], and thus consequently affect species interactions and community structure [5].…”
Section: Discussionmentioning
confidence: 99%